Anticorrosion assessment of Al2O3‐TiO2 composite thin films derived from sol‐gel dipping technique. Issue 3 (27th December 2017) - Oliaee, Seyyed Alireza; Naghibi, Sanaz
Abstract: Metal surface protection by means of nanostructured ceramic coatings is considered an issue, which is variously scrutinized, and more efforts are made to improve steel performance in accordance with this method. In this respect, this study sought to examine the protective effects of a nanostructured coating containing TiO2 and Al2 O3 . The optimization approach for obtaining a coating without any cracks with the highest efficiency of corrosion resistance is reported. The variables under assessment were as follows: weight ratio of the oxides, calcination temperature, and preparation parameters. The synthesized samples were analyzed utilizing XRD, FESEM, AFM, Tafel test, EIS, and microhardness measurement. The results revealed that the optimized conditions were as follows: (i) Ti:Al precursor mixture with a weight ratio of 75:25, (ii) heat treatment at 1000°C. This process yielded a uniform composite coating without any cracks with 5.1 nm roughness, containing crystalline rutile phase and amorphous alumina. Not only the intended coating improves the corrosion resistance of steel up to 97%, but it also increases its surface hardness up to 10 units.